The relationship between energy intake and infections in critical patients in intensive care unit (ICU) receiving medical nutrition therapy at Wahidin Sudirohusodo Hospital. - Jefri; AS’AD, Suryani; TASLIM, Nurpudji A; VERA, Desi; HUSMIANI; ABADI, Tien Muliawati; YUNITA; BUKHARI, Agussalim; AMINUDDIN; RASYID, Haerani (Nutrición Clínica y Dietética Hospitalaria, 2024)
Introduction : Nutrition is vital in caring for critically ill patients, with malnutrition closely linked to poor prognosis in ICU treatment. Objectives This study aims to establish the correlation between energy intake and infection occurrence among critically ill ICU patients undergoing medical nutrition therapy at Central General Hospital (RSUP) Dr. Wahidin Sudirohusodo. Methods : This is a retrospective cohort study on critically ill ICU patients at RSUP Dr. Wahidin Sudirohusodo Makassar, conducted from September to November 2023. The sample comprises all critical patients treated in the ICU from January 2020 to December 2022 who meet the inclusion criteria. Analysis employs One Way Anova Test and T-Test for normally distributed data, or Kruskall Wallis and Mann Whitney tests otherwise. Results : Based on the research findings, a significant correlation was found between the use of enteral and parenteral nutrition methods and the KJS or Non KJS group (p < 0.000). Specifically, enteral nutrition methods showed a significant relationship with the KJS or Non KJS group (p < 0.000), while parenteral nutrition methods also displayed a significant association (p < 0.007). Adequate energy intake is crucial for the recovery of ICU patients at RSUP dr. Wahidin Sudirohusodo, with medical nutritional therapy, including enteral or parenteral nutrition, playing a supportive role in ensuring patients receive sufficient nutrition. Conclusions : Despite similar nutritional intake, KJS patients exhibited superior bodily response, indicating the crucial role of nutritional synergy in enhancing therapy efficacy and patient outcomes.